The Strategics of Amateur Golfer Development for The Excellence - Jindapon, Suebpong (Academic Journal of Thailand National Sports University, 2022)
The research objective was to established strategic development golf amateur for excellence and to assure the validity congruity and suitability of the strategy. The research was a mix-method research design which employed qualitative and quantitative approaches. The sample was 69 golf experts including players, coaches, administrators, sponsors, and stakeholders who purposively sampling. The research instruments were interview and questionnaire. The methodology consists of: 1) interviewing about the related factors of amateur golfer development 2) SWOT analysis by conducted focus group; 3) establish strategy by researcher; and 4) validity and consensus test of the strategy by utilized Delphi technique from seventeen experts and tested index of congruence (IOC) of the strategy from 30 stakeholders. Statistical used were percentage, mean, standard deviation, mode, median, and quartile range were. The results were found that strategic development golf amateur for excellence composed of vision, mission, objective, strategy, guideline, and project. There were four strategies and eight sub-strategies: 1) player development strategy has sub-strategy 1.1 potential developing in skill technique tactics to perfection and sub-strategy 1.2 to encourage and support training and competing system which systematically implement knowledge of sports science and technology; 2) competition experience creating strategy has sub-strategy 2.1 to induce player for continuously obtain competition experience and sub-strategy 2.2 to conduct player development in every levels; 3) administrative management strategy has sub-strategy 3.1 to establish player development center, which meet international standard, for training and competing and sub-strategy 3.2 to cooperate unity among local organization for player development; and 4) encourage and support strategy has sub-strategy 4.1 to establish fund for player development and sub-strategy 4.2 to develop cooperation for fund raising from governmental and private organization. Furthermore, validity and consensus test of the strategy found that the experts mostly agreed with overall median at 5.00, quartile range between 0.00 and 0.25, index of congruence in strategies issues were between 0.69 and 0.90. In conclusion, the strategic development golf amateur for excellence from this research composed of four strategies namely 1) player development 2) competition experience creating 3) administrative management and 4) encourage and support. All strategies have very high validity and congruity. The recommendation of this research was responsive golfer development organization should apply this research findings for develop players to the accomplishment in national and international level.